Juridical Review of the Rejection of the Marriage of Isbat Convert Women from Towani Tolotang at the Sidrap Religious Court - Mutmainnah, Iin; Aris; Amir, Nurjanah (Nizham Jurnal Studi Keislaman, 2025)
This study examines the rejection of Marriage Isbat for converts from the Towani Tolotang community in Sidenreng Rappang Regency (Sidrap) in the context of the relationship between customary law, Islam, and state law. Through a normative-empirical approach, this study combines regulatory studies, Islamic law, and field data in the form of interviews with judges and affected communities. The results of the study show that the rejection of Marriage Isbat is based on incompleteness of documents, incompatibility with the pillars of marriage according to Sharia, and the status of customary marriage that has not been legally administered. The Towani Tolotang case illustrates the challenge of harmonizing the implementation of customary law, Islamic law principles, and state regulations. The Sidrap Religious Court rejected the application not because it ignored customs, but for the sake of legal certainty and the validity of sharia. The harmonization of customary and state law is an important step in ensuring legal protection for women converts and strengthening the sustainability of local cultural values in the national legal system.